Activity Test of Cassia alata L. Leaf Extract on Kidney Histopathology Damage Score of Diabetes Mellitus Model - Patala, Recky; Praypelisa, Ipa; Tandi, Jony; Utami, Indah Kurnia (Majalah Obat Tradisional, 2024)
Diabetic nephropathy is a disease experienced by diabetic patients. In this disease, damage to the glomerulus occurs. The administration of antidiabetic drugs tends to cause unwanted side effects, so there is a need for alternative treatment from herbs, one of which is Cassia alata L. Cassia alata L. leaves have chemical content such as flavonoids, alkaloids, tannins, and saponins. Flavonoids reduce blood glucose levels by increasing insulin secretion and mimetic agents, tannins slow carbohydrate digestion and saponins repair pancreatic beta cells and increase glycogen in the liver. This study aims to determine the effect of Cassia alata L. ethanol on the histopathology damage score of male white rat kidney (Rattus norvegicus) induced by streptozotocin. The test animals used were 30 male white rats divided into six treatment groups, each group consisting of five male white rats, namely the normal control group, negative control group, positive control group, treatment group with doses of 500 mg/kg BW, 600 mg/kg BW, and 700 mg/kg BW. The parameters evaluated were kidney tissue damage score and histopathology image analysis. The results showed that the ethanol extract of Cassia alata L. leaves contain alkaloids, flavonoids, saponins, and tannins. The ethanol extract of Cassia alata L. leaves in doses of 500 mg/kg BW, 600 mg/kg BW and 700 mg/kg BW has the activity of reducing the score of kidney tissue damage in male white rats and a dose of 700 mg/kg BW is the best dose in reducing the score of kidney tissue damage in diabetes mellitus models with a score of 2.